Pengaruh Profitabilitas, Leverage dan Penghindaran Pajak Terhadap Manajemen Laba pada Perusahaan Industri Barang Konsumsi di BEI Periode 2015-2019 - Andreas Cristian Halim; Maulana Malik Muhammad (UNIVERSITAS KALBIS, 2022)
The purpose of this study is to determine the effect of profitability, leverage and tax avoidance partially and jointly on earnings management in consumer goods industry companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The population in this study are all consumer goods industrial companies listed on the Indonesia Stock Exchange, totaling 53 companies. In this study, researchers only took 27 consumer goods industrial companies on the IDX in the 2015-2019 period, while the data used were financial statement data in the form of balance sheets and income statements for the 2015-2019 period. The results show that profitability has no significant effect on earnings management where H1 is rejected. Leverage has no significant effect on earnings management where H2 is rejected. Tax avoidance has a significant effect on earnings management where H3 is accepted. Profitability, leverage and tax avoidance simultaneously affect earnings management in consumer goods industrial companies listed on the Indonesia Stock Exchange in 2015-2019 H4 is accepted.